Implementation and Effectiveness of the Use of BOS Funds in Improving the Competence of Islamic Religious Education Teachers (Study at MTsS Al-Ihsan I Pragaan and MTsS Raudlatul Ulum Kapedi in 2025) - Mohammad Khoirur Rahman; Holilur Rahman (al-Afkar, Journal For Islamic Studies, 2026)
The School Operational Assistance Fund (BOS) is a government policy instrument designed to support improvements in the quality of education, including teacher competency development. In practice, BOS Fund management in madrasas is often more oriented toward administrative compliance than its strategic role in human resource development. This study aims to analyze the effectiveness of BOS Fund use in improving the competency of Islamic Religious Education (PAI) teachers at MTsS Al-Ihsan I Pragaan and MTsS Raudlatul Ulum Kapedi. This study used a qualitative approach with a descriptive-comparative design. Data were collected through in-depth interviews, observations, and documentation studies with madrasah principals, BOS Fund treasurers, PAI teachers, and other relevant parties. Data validity was ensured through triangulation of sources and techniques, while data analysis was conducted interactively through reduction, presentation, and drawing conclusions. The results indicate that the use of BOS Funds in both madrasas complies with the BOS Technical Guidelines (Juknis BOS) and is administratively effective. However, planning remains administrative in nature, PAI teacher participation is not yet strategic, competency needs identification is not systematic, and program evaluation has not been utilized as a basis for further planning. The program's impact on Islamic Religious Education (PAI) teacher competency is partial and uneven. This study concludes that the BOS Fund in both madrasas has not fully functioned as a strategic instrument for developing Islamic Religious Education (PAI) teacher competency. Strengthening the quality orientation in planning, implementation, and evaluation is needed to ensure that the BOS Fund contributes more optimally to improving the quality of learning.